The path between the seas : the creation of the Panama Canal, 1870-1914 - McCullough, David G. (Simon and Schuster Paperbacks, 1977)
Describes all the events and personalities involved in the monumental undertaking which precipitated revolution, scandal, economic crisis, and a new Central American republic.